1994
DOI: 10.1128/jb.176.2.359-367.1994
|View full text |Cite
|
Sign up to set email alerts
|

New outer membrane-associated protease of Escherichia coli K-12

Abstract: The gene for a new outer membrane-associated protease, designated OmpP, of Escherichia coli has been cloned and sequenced. The gene encodes a 315-residue precursor protein possessing a 23-residue signal sequence. Including conservative substitutions and omitting the signal peptides, OmpP is 87% identical to the outer membrane protease OmpT. OmpP possessed the same enzymatic activity as OmpT. Immuno-electron microscopy demonstrated the exposure of the protein at the cell surface. Digestion of intact cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 60 publications
(44 reference statements)
2
66
0
Order By: Relevance
“…E. coli contains two highly homologous genes encoding OmpT-like proteases: ompT on the chromosome (15) and ompP (25) on plasmid F (29). OmpP and OmpT have 87% sequence identity (25). A pgtE-specific probe hybridized to a single Salmonella genomic fragment on a Southern blot (data not shown).…”
Section: Phop/phoq Regulates Ompsmentioning
confidence: 98%
“…E. coli contains two highly homologous genes encoding OmpT-like proteases: ompT on the chromosome (15) and ompP (25) on plasmid F (29). OmpP and OmpT have 87% sequence identity (25). A pgtE-specific probe hybridized to a single Salmonella genomic fragment on a Southern blot (data not shown).…”
Section: Phop/phoq Regulates Ompsmentioning
confidence: 98%
“…2). Periplasmic fractions were generated from E. coli HB101 and UT5600, a strain which expresses high levels of periplasmic proteins but lacks the OmpT and OmpP proteases (16). The periplasmic proteins were separated by SDS-PAGE and transferred to a nitrocellulose membrane.…”
Section: Pet Binds To Periplasmic Proteinsmentioning
confidence: 99%
“…Twenty-eight of 33 fifth-round peptides contained pairs of Arg residues. Kaufmann et al (10), who first purified OmpP, reported that it cleaves primarily between consecutive basic amino acid residues in a manner not unlike that of its homologue, OmpT. Therefore, pairs of Arg/Lys residues were assigned to the P1 and P1Ј positions (Fig.…”
Section: Purification Of Omppmentioning
confidence: 99%
“…Early evidence suggested that its synthesis is regulated by phosphate and the growth temperature (10,21) and that it plays a role in the catabolism of peptides under nitrogen-limited conditions (1). The enzyme was first isolated by Henning and coworkers (10), who showed that it exhibits 71% amino acid identity with OmpT, with which it also shares a strong preference for cleavage of polypeptide substrates between pairs of basic amino acids. OmpP is stable over a broad pH range (pH 6.4 to pH 9.2) and at temperatures up to 75°C but is inactivated by Mg 2ϩ , Mn 2ϩ , Co 2ϩ , or Ca 2ϩ ions (30).…”
mentioning
confidence: 99%